Proceedings of the 2015 4th International Conference on Computer, Mechatronics, Control and Electronic Engineering 2015
DOI: 10.2991/iccmcee-15.2015.52
|View full text |Cite
|
Sign up to set email alerts
|

Research on High Efficient Utilization of LNG Cold Energy

Abstract: Abstract. Liquefied natural gas (LNG) contains a large amount of cold energy.The development of cascade utilization of LNG cold energy has large economic benefits, and it is beneficial to reduce the cost of LNG. This paper designed a process and simulated the utilization system of LNG cold energy based on the software Aspen plusin order to utilize the cold energy reasonable. The simulation results show that the cascade utilization system is rationalwhich unites the process of cryogenic comminution of waste rub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Due to the continuous demand for thermal energy, especially in winter, it would be reasonable to use the FSRU regasification plant as an economical and environmentally friendly heat sink for industrial and urban waste heat [25], as the EU has the target of climate neutrality by using waste heat. Therefore, major structural changes in FSRU are not necessary, in contrast to the proposals for its usage presented in the literature [6,8,[10][11][12][13][14][15][16][17][18][19].…”
Section: Results Of Exergy Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the continuous demand for thermal energy, especially in winter, it would be reasonable to use the FSRU regasification plant as an economical and environmentally friendly heat sink for industrial and urban waste heat [25], as the EU has the target of climate neutrality by using waste heat. Therefore, major structural changes in FSRU are not necessary, in contrast to the proposals for its usage presented in the literature [6,8,[10][11][12][13][14][15][16][17][18][19].…”
Section: Results Of Exergy Analysismentioning
confidence: 99%
“…It can be used to provide the thermal energy needed for low-temperature applications [6,10,11]. More attention is being paid to LNG cold energy systems that use this energy for electricity generation [8,12], seawater desalination [13], cryogenic air separation [14,15], freezing of material [16], carbon capture [17,18], as well as for combined LNG cold energy utilization systems [19], storage for liquid air energy [20], pumped thermal energy storage [21], etc. However, it should be noted that application of these systems needs their installation on the FSRU deck.…”
Section: Introductionmentioning
confidence: 99%
“…Yang and Wu proposed a configuration for a cold storage system using LNG cold energy and performed a feasibility analysis in terms of electricity cost [23]. Lian et al suggested a cascade system that could deliver LNG cold energy to a storage system, preventing explosion hazards [24]; Lian et al suggested possible refrigerants that could decrease the operating temperature to −60 • C, and they designed a process of a cold warehouse using LNG cold energy and conducted a thermodynamic analysis of the process [22]. Dispenza et al integrated an LNG regasification system into a power cycle and cold storage [25].…”
Section: Introductionmentioning
confidence: 99%
“…Besides power generation, as detailed in the work from (Khor et al, 2018), LNG cold energy can be used for a variety of purposes. Possible applications include air separation (Otsuka, 2006), hydrocarbon liquefaction (Otsuka, 2006), cryogenic comminution (Lian et al, 2015), production of liquid CO2/dry ice (Hongyu et al, 2010), freezing and refrigeration (Dispenza et al, 2009), seawater desalination (Dhameliya and Agrawal, 2015), and gas turbine inlet air cooling (Otsuka, 2006).…”
Section: Introductionmentioning
confidence: 99%